Penguatan Teknologi Digital di MAN 2 Garut dalam Pemikiran Islam kontemporer di Kalangan Generasi Z - Masripah, Masripah; Nazib, Fiqra; Ainissyifa, Hilda; Saifullah, Iman; rahmat, Acep; Munawaroh, Nenden; Nasrullah, Yufi; Anton, Anton; Jamal, Ahmad (Universitas Garut, 2024)
Schools Schools not only teach religions in their surroundings, but also have a social impact on the lives of their communities. This activity is carried out in MAN 2 Garut. In today's Z generation, not a few people abuse technology like the spread of incorrect information and negative influence. In addition, the unwise use of technology can also result in the exposure of content that is contrary to Islamic values, such as pornography or violence.So from that the service team to the community gives reinforcement to contemporary thinking and how to use technology well in implementing it. In addition, the purpose of this research will provide a deeper understanding of the influence of digital technology on contemporary Islamic thinking and religious practices of the Z generation in particular in MAN 2 Garut. By achieving these general and specific goals, we can formulate concrete steps that can be taken to strengthen their religious understanding, overcome the negative influence of digital technology, and maintain and properly practice authentic Islamic moral and ethical values.